Stabilizing the Oxygen Lattice and Reversible Oxygen Redox Chemistry through Structural Dimensionality in Lithium‐Rich Cathode Oxides. (19th February 2019) - Zhao, Enyue; Li, Qinghao; Meng, Fanqi; Liu, Jue; Wang, Junyang; He, Lunhua; Jiang, Zheng; Zhang, Qinghua; Yu, Xiqian; Gu, Lin; Yang, Wanli; Li, Hong; et al.
Abstract: Lattice‐oxygen redox (l‐OR) has become an essential companion to the traditional transition‐metal (TM) redox charge compensation to achieve high capacity in Li‐rich cathode oxides. However, the understanding of l‐OR chemistry remains elusive, and a critical question is the structural effect on the stability of l‐OR reactions. Herein, the coupling between l‐OR and structure dimensionality is studied. We reveal that the evolution of the oxygen‐lattice structure upon l‐OR in Li‐rich TM oxides which have a three‐dimensional (3D)‐disordered cation framework is relatively stable, which is in direct contrast to the clearly distorted oxygen‐lattice framework in Li‐rich oxides which have a two‐dimensional (2D)/3D‐ordered cation structure. Our results highlight the role of structure dimensionality in stabilizing the oxygen lattice in reversible l‐OR, which broadens the horizon for designing high‐energy‐density Li‐rich cathode oxides with stable l‐OR chemistry. Abstract : Durch Unordnung stabilisiert : Eine stabile Sauerstoff‐Gitterstruktur, die an Redoxreaktionen teilnimmt, wurde in lithiumhaltigen Kathodenmaterialien gefunden. Das ungeordnete Kationengerüst wurde mittels hochaufgelöster STEM und der Neutronen‐Paarverteilungsfunktion bestimmt. Die Stabilisierung hat ihre Ursache in der ungeordneten räumlichen Verteilung unhybridisierter O‐2p‐Orbitale.